Population ecology of the fiddler crab uca spp. in Punta, Baybay City, Leyte - Boregon, Kalvin Jay G. (Annals of Tropical Research, 2015)
A study on the population of the fiddler crabs, Uca spp. was conducted to determine their abundance, density, sex ratio, frequency and distribution pattern in the mangrove area of Punta, Baybay City, Leyte. A total of 126 individual fiddler crabs belonging to three different species were collected in a 6,000 sq m mangrove area from September to December, 2013. The three fiddler crab species were Uca perplexa, U. triangularis, and U. crassipes. Uca perplexa had the highest density which occurred only in the landward zone while U. triangularis occured in all three zones (seaward, middle and landward). The sex ratio of U. perplexa population did not deviate from the typical 1:1 ratio while U. triangularis did. In terms of their mean size, males of U. perplexa were significantly different from females while U. triangularis showed no significant size difference between males and females. Both U. perplexa and U. triangularis populations had non-normal overall size frequency distributions which were aggregately distributed. Distribution of U. perplexa population appeared to be influenced by substrate type-while U. triangularis was not affected by this parameter.